Working Documents of an Auditor and the Quality Control of Financial Reporting Made up on Foreign Investor’s Demand - V. P. Bondar (Статистика України, 2018)
Specifics of using the working documents of an auditor when auditing the financial reporting made up on external user (foreign investor) demand are highlighted. It is demonstrated by statistical data that the foreign investment in Ukraine has been growing. It follows that investors need to have confidence that the financial information used by them for making decisions on the allocation of capital is authentic and reliable, which means that a foreign investor needs high quality audit. The abovementioned increases the responsibility of an auditor for the quality of audit conclusions made by the audit results. The commonly accepted quality criterion of audit is the requirements of the International Standards on Auditing (ISA) 2015, adopted in Ukraine as national ones. As ISA do not offer specific examples regarding the format of the auditor’s working documents, a practical example is taken to demonstrate the method for quality assurance of an auditor task using check lists (working documents) in the auditing practice. An example of check list and list to the company’s administrative personnel (the customer’s administration) on the audit results is shown. The list to the customer’s administration consists of the two parts: the address to administration and the section “Report on essential comments and defects identified in the process of audit”. This section reveals the auditor’s observations on the internal control and accounting system. An example of working document “cross control”, which is used in forming the auditor’s opinion and ensures the comparability of data obtained by an auditor, is given. Being the basis for forming the auditor’s opinion, the working documents of an auditor, once unified, will reduce the labor intensity of audit procedures. It is demonstrated that the standardized working documents allow for higher quality of audit and foreign investor’s confidence.